GENETIC VARIABILITY STUDIES IN OKRA [ABELMOSCHUS ESCULENTUS (L.) MOENCH - SANGANAMONI MALLESH; REVANAPPA; S. SHIVASHANKAR; B. PRABHAKAR; VITTAL MANGI (The Bioscan, 2015)
Fifty two okra accessions were assessed to determine their genetic variability, heritability and genetic advance from twenty six parameters. The genotypic and phenotypic coefficient of variability were high for plant height at 90 days after sowing, number of nodes per plant, number of fruits per plant, rind thickness, crude fibre content, vitamin C content, seed yield per fruit and number of seeds per fruit (24.03% and 25.85%, 22.14% and 27.19%, 25.00% and 27.64%, 25.43% and 26.45%, 36.92% and 37.25%, 27.16% and 27.48%, 24.62% and 29.48% and 27.20% and 31.07% respectively) indicating maximum amount of variability present in the genotypes for these characters which would be amenable for further selection. High heritability coupled with high genetic advance over mean was observed for plant height at 45 and 90 days after sowing, number of leaves at 90 days after sowing, first flowering node, number of nodes per plant, number of fruits per plant, fruit yield per plant, average fruit weight, fruit length, fruit diameter, fruit yield per hectare, rind thickness, number of ridges on fruit surface, crude fibre content, vitamin C content, seed yield per fruit and number of seeds per fruit (71.29% and 34.00%, 86.44% and 46.03%, 72.56% and 31.61%, 91.51% and 41.19%, 66.35% and 37.16%, 81.84% and 46.60%, 74.03% and 30.86%, 72.49% and 28.44%, 91.61% and 33.75%, 88.30% and 30.83%, 74.05% and 30.86%, 92.46% and 50.37%, 96.98% and 35.95%, 98.23% and 75.38%, 97.64% and 55.29%, 76.63% and 49.05% and 69.80% and 42.38% respectively) indicates predominance additive gene action. Thus, there is ample scope for improving these characters through direct selection.